The Impact of the Ontarian Minimum Wage on the Unemployment of Women and the Young in Ontario: A Note - Cousineau, Jean-Michel; Tessier, David; Vaillancourt, François (Relations industrielles / Industrial Relations, 1992)
The purpose of this research note is to apply to Ontario a methodology developed and applied by one of the authors (Cousineau 1990) to measure the impact of Quebec's minimum wage on the unemployment of women and the young. This is of interest for two reasons. First, it allows us to examine the robustness of the methodology used by Cousineau (1990); and second, it permits us to contribute to the debate now ongoing in Ontario as to the impacts of raising the minimum wage in the province. This is of some interest, given the paucity of information on these impacts. The paper is divided into three parts. In the first one, we briefly summarize the analytical framework used. In the second, we discuss the data and variables used. In the third, we present and analyze régression results for Ontario, compare them to those obtained for Québec and use them to examine the proposed increase in the minimum wage.